2019
DOI: 10.5152/ejbh.2019.4761
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of Gene Expression Profiling in Patients with Early-Stage Breast Cancer in a Middle-Income Country, Turkey: Results of a Prospective Multicenter Study

Abstract: Objective: Breast cancer is a heterogenous disease, and genetic profiling helps to individualize adjuvant treatment. The Oncotype DX is a validated test to predict benefit of adjuvant systemic treatment. The aims of this study are to determine the costs of chemotherapy in government hospitals in Turkey and evaluate the cost-effectiveness of the Oncotype DX from the national insurance perspective. Materials and Methods:A Markov model was developed to make long term projections of distant recurrence, survival, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…This was seen in cost-effectiveness analyses of prevention strategies for breast (and ovarian) cancer through genetic testing and preventive surgery among high-risk populations (eg, relatives of affected women, Ashkenazi or Sephardic Jewish women), [20][21][22][23][24][25][26][27] screening schedules tailored to breast cancer risk, [30][31][32]34,[39][40][41]43,45 and targeting chemotherapy to women at highest risk of distant recurrence based on genomic test results. 74,75,79,[81][82][83][84] However, health care systems would require an investment of resources, training and time of providers to identify women meeting criteria for intervention, and time for counseling of women regarding the need for the intervention. None of the targeted cancer control interventions we reviewed included these types of costs, making it difficult to fully evaluate the economic value of implementing targeted care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was seen in cost-effectiveness analyses of prevention strategies for breast (and ovarian) cancer through genetic testing and preventive surgery among high-risk populations (eg, relatives of affected women, Ashkenazi or Sephardic Jewish women), [20][21][22][23][24][25][26][27] screening schedules tailored to breast cancer risk, [30][31][32]34,[39][40][41]43,45 and targeting chemotherapy to women at highest risk of distant recurrence based on genomic test results. 74,75,79,[81][82][83][84] However, health care systems would require an investment of resources, training and time of providers to identify women meeting criteria for intervention, and time for counseling of women regarding the need for the intervention. None of the targeted cancer control interventions we reviewed included these types of costs, making it difficult to fully evaluate the economic value of implementing targeted care.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles evaluated the use of new diagnostic technology, such as gene expression profile testing to guide adjuvant treatment selection. [73][74][75][76][77][78][79][80][81][82][83][84] The majority of the studies (n = 9) evaluated the cost effectiveness of the 21-gene recurrence score assay (Oncotype DX; Genomic Health, Redwood City, CA) to select treatment. 74,75,77,[79][80][81][82][83][84] Seven of these 9 studies reported cost savings or cost-effective results for Oncotype DX testing or the incorporation of Oncotype DX test results with clinical features to guide treatment decisions in patient subgroups.…”
Section: Systemic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…76,77 Kronik hastalıklar için bir çalışmada meme kanseri Markov modeli ile karar ağacı birleştirilerek uygulanmış ve erken dönem kanser hastalarında gen testi uygulanmasının maliyet-etkililiği araştırılmıştır. 78 Benzer bir çalışma, akciğer kanserinde kemoterapi ilaçları arasında maliyet açısından seçim yapmayı sağlamak adına Markov bazlı bir model oluşturmuştur. 79 Diyabet için oluşturulan bir modelle sigara ve obezite göz önüne alınarak 2025'e kadar prevalans tahmininde bulunulmuştur.…”
Section: Introductionunclassified